As representações da Balaiada na arte dos quadrinhos: a HQ Balaiada - a Guerra do Maranhão como possibilidade didática no ensino da História - Gonçalves, Elinda Maria Aguiar (2022)
This monograph aims to present the analyses of the Comic, Balaiada: The War of Maranhão both in its characteristics as an object and for its historical content, making a relationship between balaiada's historiography and the narrative represented in the language of comics. The objective is to bring approaches and didactic possibilities that can help in the teaching of the History of Maranhão. In order to bring a contribution to the construction of knowledge of regional history in a significant way to students of Basic Education, especially high school. In view of the difficulty of teaching materials that deal with this theme. In this perspective, the methodological path of this work was qualitative in nature, based on the bibliographic survey of books, theses, dissertations and articles by authors who defend comics as didactic potential in learning. It was also performed the analysis of the comic work Balaiada: A Guerra do Maranhão, and the statements of the authors of the Comic themselves through videos via Youtube and their interviews on websites.